2021
DOI: 10.1002/nur.22199
|View full text |Cite
|
Sign up to set email alerts
|

Your neighborhood matters: A machine‐learning approach to the geospatial and social determinants of health in 9‐1‐1 activated chest pain

Abstract: Healthcare disparities in the initial management of patients with acute coronary syndrome (ACS) exist. Yet, the complexity of interactions between demographic, social, economic, and geospatial determinants of health hinders incorporating such predictors in existing risk stratification models. We sought to explore a machine-learning-based approach to study the complex interactions between the geospatial and social determinants of health to explain disparities in ACS likelihood in an urban community.This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…An emerging body of research has identified both broader area level SDOH domains as well as individual level health-related social needs (HRSN) as important non-clinical drivers of health outcomes. Studies of other emergent conditions, such as sepsis, 21, 22 heart failure, 23 and acute coronary syndrome, 24 have shown that SDOH and HRSN data can be important for identifying drivers of disparities in outcomes and improving prediction specific clinical endpoints for patients. Specific to OHCA, a study examining 22,816 patients contained within the Resuscitation Outcomes Consortium (ROC) database found predominantly neighborhoods with a greater proportion of Black individuals were associated with lower rates of survival to hospital discharge when compared with neighborhoods with a greater proportion of White individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging body of research has identified both broader area level SDOH domains as well as individual level health-related social needs (HRSN) as important non-clinical drivers of health outcomes. Studies of other emergent conditions, such as sepsis, 21, 22 heart failure, 23 and acute coronary syndrome, 24 have shown that SDOH and HRSN data can be important for identifying drivers of disparities in outcomes and improving prediction specific clinical endpoints for patients. Specific to OHCA, a study examining 22,816 patients contained within the Resuscitation Outcomes Consortium (ROC) database found predominantly neighborhoods with a greater proportion of Black individuals were associated with lower rates of survival to hospital discharge when compared with neighborhoods with a greater proportion of White individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Our special issue, similarly, highlights the importance of considering the residential neighborhood and housing status when evaluating utilization and access to health care. Using a machine learning approach Faramand et al (2021) found that residential neighborhood and distance to hospital predicted disparities among Black acute coronary syndrome patients. Similarly, in their study of nurse and case managers, Schneiderman et al (2021) noted that healthcare utilization among previously unhoused individuals was shaped by a complex interplay of trauma related to previous homelessness, financial insecurity, and negative interactions with healthcare providers.…”
mentioning
confidence: 99%